We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
148
1
avatar

(21/2  + 2)2  - 25/2

 Sep 22, 2018
 #1
avatar+99461 
+1

 

 

(2 ^(1/2) + 2)^2  - 2^(5/2)    =         [ a^2  = a* a ] 

 

(2^(1/2)  + 2) (2^(1/2) + 2)  - 2^(5/2)   =

 

2^(1/2) * 2^(1/2)  * 2*2^(1/2) + 2*2^(1/2)  + 2 *2   - 2^(5/2)  =    [ We are using   a*m * a^n   = a^(m + n) ]

 

2^(1)    +  4*2^(1/2) + 4   - 2^(5/2)  =


6  + (2)^2 * 2^(1/2)  - 2^(5/2)  = 

 

6 + 2^ (2 + 1/2)  - 2^(5/2)

 

6  + 2^(5/2)  - 2^(5/2)   =

 

6

 

 

cool cool cool

 Sep 22, 2018

16 Online Users

avatar